Congenital triangular alopecia: Clinical and dermoscopic differentials - Vishalakshi Viswanath; Vaibhav Kalambe; Dhananjay Sanap (Wolters Kluwer Medknow Publications, 2019)
Congenital triangular alopecia (CTA), also known as temporal triangular alopecia; originally described by Sabouraud in 1905; is a type of triangular, unilateral, nonprogressive, noncicatricial type of alopecia affecting mostly the temporal region of the scalp. It usually presents at birth or in early childhood, however adult cases have also been reported. Routinely confused with alopecia areata; dermoscopy helps in the diagnosis of this condition. We report a case of CTA with clinical and dermoscopic findings and discuss the differential diagnosis.